Anesthetic Cream Use During Office Pessary Removal and Replacement: A Randomized Controlled Trial. Issue 10 (October 2017) - Taege, Susanne K.; Adams, William; Mueller, Elizabeth R.; Brubaker, Linda; Fitzgerald, Colleen M.; Brincat, Cynthia
Abstract : (Abstracted from Obstet Gynecol 2017;130:190–197) An inexpensive, nonsurgical treatment option for pelvic organ prolapse and stress urinary incontinence is the vaginal pessary; these are especially for women with severe medical comorbidities that make them poor surgical candidates. Although attempts at pessary fitting are successful in nearly 90% of patients, approximately half discontinue use within 24 months after fitting.